PERKEMBANGAN PEMIKIRAN PENYELESAIAN SENGKETA PADA EKONOMI SYARIAH DI INDONESIA - Ayi Nurbaeti; Ahmad Lukman Nugraha; Ismayadi (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2022)
Abstract-Al-Quran, As-Sunnah and Ijma are the basis for deciding cases in courts that have been prescribed by religion. Allah SWT ordered to decide the law or punish mankind with what was revealed by Allah. Prophet Muhammad directly adjudicate and punish cases that arise in the midst of society with the laws of Allah. Prophet Muhammad SAW also gave decisions on several issues such as the issue of hisbah when he found a trader in the market who mixed wet wheat with dry wheat; in matters concerning pricing; in a dispute between Zubair bin Awwam and an Ansar over irrigation issues and so on. As the era of economic development is getting more complex and the potential for complications or disputes is also getting bigger, for that we need an agency or several institutions that can handle these disputes, this is different when the Prophet decided cases. The development of sharia economic activities and their settlements is also growing rapidly in Indonesia, such as the settlement of sharia economic disputes which is the authority of the Religious Courts, besides that it can be based on PERMA Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Cases. The long journey of resolving disputes over Islamic Economics midwives from the time of the prophet to the present.